LOCAL ECONOMIC DEVELOPMENT STRATEGY THROUGH HUMAN RESOURCE EMPOWERMENT IN THE MSME SECTOR IN MEDAN CITY - Fadillah, Tri Dessy; Khairina,; Arfan Ikhsan,; Nazli Aisyah Amin, (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
This study aims to analyze local economic development strategies through human resource empowerment in the MSME sector in Medan City. The methodology of this research employs a descriptive qualitative approach, collecting data from primary sources by distributing questionnaires to respondents using the pentahelix collaboration model (ABCGM), comprising academics, businesspeople, communities, government, and media. Analysis technique by analyzing the integration of SOAR matrix strategies (Strength, Opportunity, Aspiration, and Result). The results of the analysis show that the MSME development strategy produces four strategies, namely: (1) comprehensive training and mentoring programs for human capital formation, (2) development of the MSME digital ecosystem towards a knowledge-based economy, (3) strengthening the PentaHelix collaboration (ABCGM) as a governance innovation, and (4) developing industrial clusters based on local potential for regional competitive advantage. The study's findings have profound implications for the development of MSME policy at local, regional, and national governance levels. The validated strategic framework provides compelling evidence in support of integrated policy approaches that deliberately transcend traditional sectoral boundaries and administrative silos, arguing for comprehensive policy coordination mechanisms that address MSME development as a complex, interconnected challenge rather than a series of discrete problems. The research highlights the critical importance of developing an institutional framework, suggesting that policy attention should prioritize governance structures and coordination mechanisms over narrowly focused program-specific interventions that fail to address systemic constraints on MSME growth and competitiveness.